Transport and Assembly of Particles by Nematic Liquid Crystal Phase Boundary - Shneer, Tom. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023.; Submitted to the Dept. of Physics.; Advisor: Timothy Atherton.; Committee: Hugh Gallagher, Cristian Staii, Peggy Cebe, and Timothy Atherton.; Keywords: Physics, Condensed matter physics, and Theoretical physics.